An anatomical variation in the branching pattern of the coeliac trunk - Mahajan, Anita; Paul, Shipra; Das, Srijit (Archives of Medical Science, 2009)
The coeliac trunk gives off three branches, i.e. the splenic artery, the hepatic artery and the left gastric artery. In the present study, we report two additional branches arising from the coeliac trunk. Of the two branches, the larger branch (accessory hepatic artery) traversed to the right, passing posterior to the portal vein, thereby ascending along the left margin of the common bile duct, while the smaller branch supplied the common bile duct (retroportal artery). Anatomical knowledge of the anomalous branching pattern of the coeliac trunk may be important for surgical, interventional and radiological purposes